Report on proposed new design of Kawasaki Sales and Service centre for Kawasaki Motors Malaysia Sdn. Bhd. at No 122, Jalan Sultan Abdul Jalil Greentown, 30450 Ipoh perak / Mohd Azhari Mohd Arsat - Mohd Arsat, Mohd Azhari (Faculty of Architecture, Planning and Surveying, 2010)
As a final year student in diploma of Interior Architecture, the student is required to prepare a final project design. The design of the project should be based on the current issues. The knowledge and skill acquired during the duration of the course should be put to practise and onto the drawing board. This also includes the research, case study, interviewing of clients, designing proposals, preparing art work, preparing presentation drawings, design development and last but not least the final presentation. The project selected is to proposed new design of Kawasaki Sales and Service Centre at no 122, Jalan Sultan Abdul jalil, Greentown Ipoh, Perak. The idea to proposed this project is because the increased production of Kawasaki motorcycle by Kawasaki Motors (Malaysia) Sdn Bhd and there is no Kawasaki Sales and Service Centre ever built at north side of peninsular Malaysia, a plan was proposed to prepare a sales and service centre using the requirement and needs for both of client and customers. From the research and observation conducted on the product and the site, the information and details gathered was used as a guideline to prepare the design. After surveying in a while, a building in Greentown Ipoh had been selected as a proposed site for this project. The objective is to proposed new design for Kawasaki Slaes and Service centre and create space with new environment. Which is consist to the company image and emphasizing the company image to the customer. The design should be attractive to attract the customers at the north side of Peninsular Malaysia.